Association between platelet count and osteoarthritis in women older than 50 years. (March 2020) - Kwon, Yu-Jin; Koh, Il-Hyun; Chung, Kwangho; Lee, Yong-Jae; Kim, Hyoung-Sik
Background: Osteoarthritis (OA) is a multifactorial disease involving inflammatory processes. Platelets play important roles in both hemostasis and the inflammatory response; however, the relationship between platelet count and OA is unclear. Our aim was to evaluate the association between platelet count and knee and hip OA in Korean women. Methods: In this cross-sectional designed study, we included a total of 6011 women aged ⩾50 years from the 2010–2013 Korea National Health and Nutrition Examination Survey. Knee and hip OA were defined as Kellgren–Lawrence grade ⩾2 and presence of knee or hip pain, respectively. Platelet counts were divided into quartiles as follows: Q1, 150–212 (10 3 /µl); Q2, 213–246 (10 3 /µl); Q3, 247–283 (10 3 /µl); and Q4, 284–450 (10 3 /µl). Multiple logistic-regression analysis was conducted to calculate odds ratios and 95% confidence intervals. Receiver operating characteristic analysis was performed to determine the optimal platelet count cut-off with which to discriminate participants with knee and/hip OA versus those without OA. Results: Of the 6011 participants, 1141 (18.1%) had knee or hip OA. The mean age of participants without OA was 60.6 years, and that of participants with OA was 68.0 years. Compared with the lowest quartile, odds ratios (95% confidence intervals) for OA were 1.08 (0.84–1.39) for Q2, 0.94 (0.73–1.23) for Q3, and 1.35 (1.08–1.69) for Q4 after adjusting for confounders. The prevalence of OA was significantly higher with platelet counts ⩾288 × 10 3 /µl, compared with platelet counts <288 × 10 3 /µl. Conclusion: High platelet counts within the normal range are significantly associated with knee and hip OA.